Impact of social media on medical education as assessed by a structured questionnaire among medical students of a medical college in a metropolitan city - Bharadwaj Arun, Pranav; Jannavada, Hasitha (International Journal Of Community Medicine And Public Health, 2025)
Background: The integration of social media into medical education has redefined access to and dissemination of knowledge. Platforms such as YouTube, WhatsApp, Instagram, and Telegram are increasingly used for collaborative discussions, exam preparation, and procedural learning. In urban India, where internet access is widespread, understanding its impact on medical education is highly relevant. This study assessed patterns of social media usage among medical students enrolled in a metropolitan medical college, examined the educational relevance of their social media content, and evaluated students’ perceptions of social media as a learning tool. Methods: A cross-sectional study was conducted using an online questionnaire with both open- and closed-ended questions among undergraduate students at a tertiary hospital in Bengaluru. A total of 117 responses were analysed using descriptive statistics. The survey examined platform use, content relevance, recall, behavioural influence, and overall attitudes. Results: YouTube (98.3%), WhatsApp (97.43%), and Instagram (83.76%) were the most used. While 60.68% spent 1-3 hours daily, only 5.99% crossed 6 hours. About 58.12% reported 26-50% medically relevant feeds. Students preferred “edutainment”: 70.94% engaged with memes, and 56.41% with mnemonics. Although 83.76% believed social media improved education and 63.25% recalled better than lectures, 76.1% admitted to poor long-term retention. Only 36.75% said it helped pass exams. Conclusions: Social media is an engaging and beneficial adjunct to medical education, but is limited by retention and accuracy. Structured integration, student-led creation, and regulatory oversight can optimise its academic utility.